2016
DOI: 10.1371/journal.pone.0166728
|View full text |Cite
|
Sign up to set email alerts
|

Low Birth Weight Is Associated with a Decreased Overall Adult Health Status and Reproductive Capability – Results of a Cross-Sectional Study in Primary Infertile Patients

Abstract: Individuals born with low birth weight (LBW) risk cardiometabolic complications later in life. However the impact of LBW on general health status and male reproductive function has been scantly analysed. We investigated the clinical and seminal impact of different birth weights (BW) in white-European men presenting for primary couple’s infertility. Demographic, clinical, and laboratory data from 827 primary infertile men were compared with those of 373 consecutive fertile men. Patients with BW ≤2500, 2500–4200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 36 publications
0
20
0
1
Order By: Relevance
“…[6][7][8][9][10][11] Being born small for gestational age and having low birth weight are common features among patients with hypospadias [12][13][14] and have also been suggested to increase the risk of subsequent male infertility and need of assisted reproductive technologies (ART). 15,16 Paternal subfertility and the use of ART are suggested risk factors for hypospadias, and it is plausible that subfertility traits in the father may be transferred to the son. 17,18,19,20 As previously mentioned, few previous studies have investigated the paternity rate in men with hypospadias.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] Being born small for gestational age and having low birth weight are common features among patients with hypospadias [12][13][14] and have also been suggested to increase the risk of subsequent male infertility and need of assisted reproductive technologies (ART). 15,16 Paternal subfertility and the use of ART are suggested risk factors for hypospadias, and it is plausible that subfertility traits in the father may be transferred to the son. 17,18,19,20 As previously mentioned, few previous studies have investigated the paternity rate in men with hypospadias.…”
Section: Introductionmentioning
confidence: 99%
“…These infertile LBW men had reduced sperm motility and abnormal sperm morphology, lower total testosterone levels but higher FSH values, compared with average or high birth weight men. Interestingly, these LBW male patients reported a higher rate of significant comorbidities and reduced left testicular volume and also presented with higher BMI (Boeri et al 2016). It may be that part of association between reproductive deficits and LBW could be accounted for by an increased prevalence of obesity, which occurs concomitantly with metabolic dysfunction, since LBW increases obesity risk, and obesity in men is known to impair reproductive capacity (Palmer et al 2012).…”
Section: High Fat Fetusesmentioning
confidence: 97%
“…86 Recently, a cross-sectional study observed reduced sperm motility and higher rates of abnormal sperm morphology, including asthenozoospermia and teratozoospermia in adult infertile individuals born with low birth weight. 11 Other findings were higher follicle stimulating hormone (FSH) values, lower mean testicular volume, as well as lower testosterone levels in adulthood. 87 Although there are controversies regarding the relationship between the developmental environment and postnatal reproductive function in men, this evidence suggests that early life events may contribute to male infertility.…”
Section: Fetal Programming and The Male Reproductive Systemmentioning
confidence: 99%
“…5,8,10 For example, a cross-sectional study has shown that low birth weight is associated with decreased overall adult health status as well as reduced reproductive capability. 11 Although birth weight is a poor proxy for nutritional events during gestation, the Barker hypothesis has been confirmed in many independent cohorts across the developed and developing world. [12][13][14] Similarly, the 'thrifty phenotype' hypothesis proposes that poor fetal nutrition imposes mechanisms of nutritional economy upon the growing individual.…”
Section: Introductionmentioning
confidence: 97%